DEVELOPMENT OF PROBLEM BASED LEARNING-BASED EMODULES TO IMPROVE CRITICAL THINKING ABILITIES OF STUDENTS OF CLASS X SMAN 1 KOTA TANGERANG - Nurhidayat, Fachri; Saptono, Ari; Herlitah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to determine: (1) the feasibility of economic problem based learning (PBL) e-modules; (2) find out of differences critical thinking skills of students who use e-modules and students who dont use e-modules. This research used research and development (R&D) using a development design from ADDIE. The subjects of this study were students of class X IIS 2 with 38 students as the experimental class and X IIS 1 with 39 students as the control class. Product testing uses a posttest only control design. The analysis technique used the Mann Whitney test because the data were not normally distributed. The results of the study show: (1) the developing of economic problem based learning e-module is categorized as very feasible. (3) there are differences in critical thinking skills of student between the experimental class and the control class based on the Asymp Sig score. (2-tailed) of 0.000<0.05. So it can be concluded that problem based learning e-modules can improve critical thinking skills of student.